Influencer Marketing Strategy in Sharia Marketing: A Review from the Perspective of Ethics and Sharia Values - Suraya, Ismi; Zulfikar, Faisal (El-Barka Journal of Islamic Economics and Business, 2025)
A common form of digital marketing today involves promoting products through influencer marketing strategies, carried out by individuals known as influencers. However, the application of influencer marketing often fails to align with Islamic ethical values, as seen in the lack of transparency or honesty, promotion of non-halal products, inadequate product descriptions, exaggerated claims, and the inappropriate appearance or attire of some influencers. These issues can lead to legal disputes and leave consumers feeling harmed. Therefore, clear guidance on the ethical conduct and behavior of influencers is essential. This study applies the Stimulus-Organism-Response (S-O-R) theory and uses a qualitative method with a descriptive approach. The data is composed of written words drawn from in-depth phenomena within the relevant context. Secondary data sources include books, academic journals, websites, and online resources. The findings reveal that influencer marketing is effective in building trust and enhancing marketing outcomes. Its effectiveness increases when aligned with sharia principles, such as honesty, transparency, and the promotion of halal and beneficial products. Consumer responses are heavily influenced by the ethics and values demonstrated by the influencer. Hence, in sharia-based marketing, influencers serve not only as promotional agents but also as representatives of Islamic values, contributing to transactions that yield not just economic benefits but also positive social and spiritual impacts.